Traditional knowledge and uses of Argemone mexicana L. (Papaveraceae) in southern Benin - Gbesso, Gbodja Houéhanou François; Gbesso, Florence Koussi; Adoukonou, Ruddy Chancelle Fleur; Akabassi, Ghislain Comlan; Padonou, Elie Antoine; Tente, Agossou Brice Hugues (Ethnobotany Research and Applications, 2021)
Background: Argemone mexicana is an important medicinal plant species used by local people to treat several diseases. Despite its importance, the species faces serious conservation problem. This study was conducted in southern Benin to assess the traditional knowledge and uses of A. mexicana within four socio-cultural groups. Methods: Ethnobotanical surveys were conducted in local communities with 130 informants randomly selected among four socio-cultural groups namely Fon, Adja, Mahi, and Nago/Yorouba. The interview was performed in local language. Ethnobotanic parameters were calculated to assess the knowledge and use of the species. Hierarchical Cluster Analysis followed by Correspondence Analysis (CA) were used to show the relation between the surveyed populations, diseases treated and the involved organs. Results: Local community members of the four socio-cultural groups used the different parts of A. mexicana for 12 treatments. The leaves of the species were the most organ used followed by the whole plant. The socio-cultural group Fon had better knowledge of the uses of the species compared with others. The old men/women tradi-practitioner had the best knowledge on the species. A. mexicana was only present in agroforestry systems. The deforestation was the main threat of the conservation of the species. Conclusion: This study demonstrates the use of A. Mexicana in Southern Benin. The result could be used to develop specific sustainable utilization and conservation strategies of A. Mexicana within local communities of Benin. Keywords: Argemone mexicana, ethnobotany, conservation, Benin